Barrett’s Esophagus: Is It All That Bad? - GNJ Tytgat (Canadian Journal of Gastroenterology)
An alarmingly rapid rise in the number of adenocarcinomas at the level of the gastroesophageal junction and distal esophagus has been noted over the past two decades. Intestinal metaplasia is considered to be the main precursor lesion for such adenocarcinomas. Given the low five-year survival rate in patients with advanced esophageal cancer, strategies for early detection have been developed. Because superficial cancers only rarely cause symptoms, detection of cancer at such an early curable state can only be achieved through surveillance of patients at risk. Therefore, implementation of an endoscopic surveillance program for patients in whom intestinal metaplasia has been detected in the distal esophagus or at the esophagogastric junction seems to be a reasonable option.